Respuesta :

Given the function:

[tex]f\mleft(x\mright)=-3x+7[/tex]

And the function:

[tex]g\mleft(x\mright)=2x^2-8[/tex]

You can find

[tex]f\mleft(x\mright)-g\mleft(x\mright)[/tex]

By subtracting both functions.

Then, you can set up that:

[tex]f(x)-g(x)=\mleft(-3x+7\mright)-\mleft(2x^2-8\mright)[/tex]

Now you must distribute the negative sign:

[tex]f(x)-g(x)=-3x+7-2x^2+8[/tex]

And finally, you must add the like terms (Remember that, by definition, the "Like terms" are those terms that have the same variables and the same exponent). Therefore, you get:

[tex]f(x)-g(x)=-2x^2-3x+15[/tex]

The answer is: Option A.

ACCESS MORE
EDU ACCESS